Medicine and the Market in England and its Colonies, c.1450- c.1850
XIII, 269 p.
Keywords: What was the medical marketplace? This book provides the first critical examination of medicine and the market in pre-modern England, colonial North America and British India. Chapters explore the most important themes in the social history of medicine and offer a fresh understanding of healthcare in this time of social and economic transformation.